2020
DOI: 10.3390/jcm9082509
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Tissue MIR92a and Plasma MIRs21 and 29a as Predictive Biomarkers Associated with Clinicopathological Features and Surgical Resection in a Prospective Study on Colorectal Cancer Patients

Abstract: Cancer-related microRNAs (miRNAs) are emerging as non-invasive biomarkers for colorectal cancer (CRC). This study aimed to analyze the correlation between the levels of tissue and plasma miRNAs and clinicopathological characteristics and surgical resection. This study was a prospective study of CRC patients who underwent surgery. Forty-four sample pairs of tissue and plasma were analyzed. The miRNA levels were evaluated by RT-qPCR. The level of tumor tissue MIR92a showed a significant difference in CRC with ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…We previously estimated the plasma levels of several miRNAs in these patients. 8 Among the miRNAs tested, we focused on plasma miR21‐5p levels by performing qRT‐PCR between pre‐ and post‐surgical resection. In the recurrence and PD group, the plasma miR21‐5p level showed a significant increase after surgical resection at POM1 and POM6 (POD7: P = .19, POM1: P < .01, and POM6: P < .01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously estimated the plasma levels of several miRNAs in these patients. 8 Among the miRNAs tested, we focused on plasma miR21‐5p levels by performing qRT‐PCR between pre‐ and post‐surgical resection. In the recurrence and PD group, the plasma miR21‐5p level showed a significant increase after surgical resection at POM1 and POM6 (POD7: P = .19, POM1: P < .01, and POM6: P < .01).…”
Section: Resultsmentioning
confidence: 99%
“…We previously estimated the plasma levels of several miRNAs in these patients 8 . Among the miRNAs tested, we focused on plasma miR21‐5p levels by performing qRT‐PCR between pre‐ and post‐surgical resection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported that miRNA levels in plasma and tumor tissue showed significant differences. A strong correlation between expression levels of miRNA in colon tumor tissue and levels of fecal miRNAs were found, but not between levels of miRNAs in colon tumor and plasma [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA (miRNA) is one of the epigenetic regulators of gene expression for specific genes associated with cancer progression, such as cell proliferation, cell invasion, and metastasis in numerous cancers, including gastric cancer 3 5 . Some miRNAs function as tumor suppressive miRNA by inhibiting c-MYC , one of the most studied oncogenes that promote cancer cell proliferation 6 , 7 , such as miR-429 8 and miR-494 9 .…”
Section: Introductionmentioning
confidence: 99%